A Finite-Element-Based Investigation of the Influence of the Production Environment on Fuel Cell Membrane Electrode Assemblies During Manufacturing - Ling Ma; Zhuoqi Yan; Sebastian Schabel; Jürgen Fleischer (Energies)
The manufacturing process for membrane electrode assemblies (MEAs), from coating to stack assembly, is typically performed under climate-controlled conditions due to the hygroscopic properties of catalyst-coated membranes (CCMs). Large climate-controlled areas in the assembly line not only increase the energy consumption but also limit the scalability of the production line. In this study, experiments were conducted to analyze the effects of ambient humidity on the mechanical properties of a CCM. The hygroscopic swelling behavior of a commercial CCM with an ePTFE-reinforced membrane was also characterized. Using the finite element method, a 3D numerical model covering the entire MEA assembly process was developed, allowing for a numerical investigation of different climate control strategies. The influence of ambient humidity on the dimensional changes in the CCM, which leads to significant stress on the CCM due to mechanical constraints and thus to deformation of the MEA product, was simulated and validated experimentally using optical measurements. Finally, the critical steps during MEA assembly were identified, and a recommendation for the optimal humidity range for climate control was derived.